Hardy type unique continuation properties for abstract Schrödinger equations and applications - Veli Shakhmurov (Electronic Journal of Qualitative Theory of Differential Equations, 2019)
In this paper, Hardy's uncertainty principle and unique continuation properties of Schrödinger equations with operator potentials in Hilbert space-valued $L^{2}$ classes are obtained. Since the Hilbert space $H$ and linear operators are arbitrary, by choosing the appropriate spaces and operators we obtain numerous classes of Schrödinger type equations and its finite and infinite many systems which occur in a wide variety of physical systems.